PEMIKIRAN HAMKA DALAM NOVEL-NOVELNYA: SEBUAH KAJIAN SOSIOLOGIS - Armini Arbain (Universitas Andalas, 2017)
In this article is discussed about the thought of Hamka contained in his novels. Hamka a man who has a multitalenta as a writer, thinker, writer, historian, and mufasir. That is, a Hamka not only as a writer but also as a thinker, writer, mufasir (interpreter of the Qur'an) and historian at the same time. The unification of the five qualities as above would be complementary to each other. Thus, when Hamka concocted a novel, her qualities as a thinker. writers, mufasir and historians will accumulate into his fictional work so that in the work of his novels there are a number of pithy thoughts. A number of thoughts contained in his fictional works can not be separated from the social realities of Hamka's life. Keywords: Thought, Hamka, works of fiction, and social reality